Arthroscopic Mobilization of the Ankle-subtalar Joint Complex Using a Novel "Infra-fibula-tip" Portal. Issue 4 (22nd October 2020) - Tochigi, Yuki; Ozeki, Satoru; Ogawa, Masato
Category: Arthroscopy; Hindfoot Introduction/Purpose: As a minimally invasive surgical option for posterior ankle/subtalar pathologies, the prone hindfoot endoscopy (a.k.a. Van-Dijk's method) has been becoming the 'gold standard' technique. While this technique holds advantage regarding good orientation and safety handling of posteromedial pathologies, it limits access to the anterolateral part, therefore inconvenient when simultaneously dealing with anterior and posterior pathologies. Recently, we have introduced a novel 'infra- fibula-tip (IFT)' portal, which permits wide access to the posterior talocalcaneal joint (PTCJ), from anterolateral to posteromedial, with a patient positioned in supine or semi-lateral. The present study reviewed clinical outcomes of a case series of arthroscopic hindfoot mobilization using this new surgical technique, so as to document its clinical utility. Methods: The sequence of surgical procedures is as follows; - Create an IFT portal, from a small incision immediately distal to the fibular tip, through the peroneal tendon sheath (anterior to the tendons, but posterior to the calcanofibular ligament), toward the posterior porch of PTCJ. - Inserting a 30-deg 2.7mm scope to the posterior porch, and broadly observing posterior intraarticular findings. - Gently moving the scope to the anterolateral porch, and broadly observing anterolateral intraarticular findings. - Creating an anterolateral (AL) portal under arthroscopic guidance. - Creating a PL portal at immediately lateral to the Achilles tendon, with guidance of a blunt rod inserted from the AL portal (gently advanced posteriorly through the lateral recess and penetrated the rod toward subcutis). - Executing posterior procedures from the PL portal, while observing from the IFT portal. Executing anterolateral procedures working from the AL portal, while observing from the IFT portal. Results: A total of 7 cases underwent the procedure of interest to date. Subtalar osteoarthritis (OA) occurred in all, with accessory anterolateral talar facet (AALTF) impingement in 3. Ankle OA occurred in 3, with anterior bony impingement in 2. Preceding pathologies included peri-ankle intraarticular fractures (4), talocalcaneal coalition (2), and neurogenic varus foot (1). Mobilization procedures included lateral-to-posterior PTCJ debridement (7), coalition release (2), AALTF removal (3), sinus debridement (2), posterior ankle capsule release (2), anterior ankle debridement (2), talonavicular debridement (1), and Achilles tendon lengthening (1). The surgery duration ranged from 65 to 245 minutes. Postoperatively, of 4 cases followed more than 6 months, remarkable motion improvement (10 degrees or more) occurred in 3, and every case reported symptom relief. Conclusion: The IFT portal accesses the middle of the PTCJ, with a short skin-to-joint distance, allowing flexible exploration of both the posterior and anterior porches. Posteriorly, ability of direct intraarticular access (without extraarticular shaving) reduces surgical invasion, as well as the risk of potential neurovasucular injury. Anteriorly, it helps secure good triangulation for handling sinus pathologies. Since subtalar arthroscopy using the IFT portal is doable in a supine or semi-lateral position, anterior ankle arthroscopy could be simultaneously executed. Arthroscopic hindfoot mobilization using this technique appears to be efficient for dealing with ankle/subtalar contracture due to combined anterior and posterior pathologies.